Teaching English To Non-English Students' Department At Islamic University Of Indonesia Through Formula 33: Students' Reflections - Sadiq, Nizamuddin (Journal of English and Education (JEE), 2012)
Results of students' need analysis show that grammar (tenses) is the students' lowest ability that they wanted to learn at that time. In order to cope with that contextual situation, Formula 33 is proposed to be the main concern on the learning English for students of non-English deparment at Islamic University in the academic year 2012/2013. Students must write reflections - express their emotion and knowledge gain in the form of essay to e-learning provided - every time the class end. The students' reflections were considered as data. The data were classified based on some categories/themes descriptively. Those data are then read very carefully to find out the keywords that became the instruments to classify them into themes, while irrelevant data were sorted. The results show that learning English through Formula 33 addressed in three aspects - learning domain, teaching delivery, and students' best practice. In learning domain, students have positive and negative cognitive feedback. Formula 33 was considered improving their skills especially in writing English sentences with correct grammatical structure as well as they have excellent attitude toward Formula. In teaching delivery that consists of two keywords method and materials. Students said that both method and materials are super.Key words: Formula 33, positive and negative cognitive feedback, teaching delivery